The Availability of Entrepreneurial Alertness Dimensions in the Northern Technical University and its formations in Nineveh Governorate: A diagnostic analytical study of the opinions of a sample of administrative leaders (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The research aims to determine the availability of the dimensions of entrepreneurial alertness represented by (survey and research, cooperation and communication, evaluation and governance) among the leaders of the Northern Technical University and its formations in Nineveh Governorate. The descriptive analytical approach was adopted in processing the data collected through a questionnaire distributed to a sample consisting of (85) Respondents representing the senior and middle administrative leadership in the researched organizations, and several statistical methods were used in analyzing this data according to the ready-made software (SPSS V. 25). The research reached several results that confirmed the availability of these dimensions at high levels among the leaders of the researched organizations, in addition to presenting a group Among the proposals that emphasize the necessity of strengthening the ownership of these dimensions by the leaders of the researched organizations and working to adopt them in order to achieve their goals.